PATIENT WITH VERUCCA VULGARIS RECCURENT - Gita Saraswati, Ni Made (E-Jurnal Medika Udayana; vol 2 no6(2013):e-jurnal medika udayana)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 The common wart or verruca vulgaris are benign lesions, elevated, firm nodules with characteristic papillomatous surface projections. This lession could appear anywhere in the body, mostly in fingers. The lesion could spread anywhere in the body, leaving a scar and also have a high incidence of reccurency. This report describe a man with verruca vulgaris recurrent. Preventive is important to prevent the reccurency, beside electrodesication as a curative therapy. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: verucca vulgaris, warts, electrodesication